2024
DOI: 10.1371/journal.pone.0297466
|View full text |Cite
|
Sign up to set email alerts
|

Application of the integrated gateway model on child nutrition behaviors in Niger: An exploratory analysis

Leanne Dougherty,
Chaibou Dadi

Abstract: Objective To identify potential gateway factors and behaviors that are associated with infant and young child feeding (IYCF) practices in the Maradi and Zinder regions of Niger through application of the Integrated Gateway Model. Methods We analyzed data from 2,727 married women of reproductive age including details on child feeding practices for their 2,551 children between the ages of 0 to 23 months. We assessed the association of three gateway behaviors (i.e., any antenatal care, facility delivery, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The role that the health facility and providers played in sharing health messages, however, proved promising. Previous studies have found leveraging health system interactions [ 34 , 35 ] and integrating demand creation program with supply side interventions can lead to improvements in health outcomes [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role that the health facility and providers played in sharing health messages, however, proved promising. Previous studies have found leveraging health system interactions [ 34 , 35 ] and integrating demand creation program with supply side interventions can lead to improvements in health outcomes [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%